2013
DOI: 10.1111/peps.12021
|View full text |Cite
|
Sign up to set email alerts
|

Service Employees’ Reactions to Mistreatment by Customers: A Comparison Between North America and East Asia

Abstract: The authors proposed that customer service employees’ reactions to mistreatment by customers can vary between North American and East Asian employees due to differences in their cultural values. Customer mistreatment was predicted to be associated with direct, active, and target‐specific reactions (i.e., sabotage directed toward the source of mistreatment) more so among North American employees as compared to East Asian employees. In contrast, customer mistreatment was predicted to relate to more indirect, pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
228
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(238 citation statements)
references
References 86 publications
(141 reference statements)
8
228
1
1
Order By: Relevance
“…Consistent with previous empirical studies documenting the effects of resource depletion, customer mistreatment has been linked with employee sabotage (Shao & Skarlicki, 2014;Wang et al, 2011), incivility toward customers, job demands (van Jaarsveld, Walker, & Skarlicki, 2010), withdrawal (e.g., absences, Grandey et al, 2004), reduced performance (e.g., Sliter, Sliter, & Jex, 2012), and burnout (e.g., Ben-Zur & Yagil, 2005;Dormann & Zapf, 2004;Grandey et al, 2007;Greenbaum, Quade, Mawritz, Kim, & Crosby, 2014). For example, Wang et al (2011), using a sample of call center employees, reported that customer mistreatment was positively related to employee sabotage and this positive association was mitigated by job tenure (i.e., cognitive resource) and service rule commitment (i.e., motivational resource).…”
Section: Customer Mistreatment As a Resource-depleting Eventsupporting
confidence: 75%
See 2 more Smart Citations
“…Consistent with previous empirical studies documenting the effects of resource depletion, customer mistreatment has been linked with employee sabotage (Shao & Skarlicki, 2014;Wang et al, 2011), incivility toward customers, job demands (van Jaarsveld, Walker, & Skarlicki, 2010), withdrawal (e.g., absences, Grandey et al, 2004), reduced performance (e.g., Sliter, Sliter, & Jex, 2012), and burnout (e.g., Ben-Zur & Yagil, 2005;Dormann & Zapf, 2004;Grandey et al, 2007;Greenbaum, Quade, Mawritz, Kim, & Crosby, 2014). For example, Wang et al (2011), using a sample of call center employees, reported that customer mistreatment was positively related to employee sabotage and this positive association was mitigated by job tenure (i.e., cognitive resource) and service rule commitment (i.e., motivational resource).…”
Section: Customer Mistreatment As a Resource-depleting Eventsupporting
confidence: 75%
“…In addition, customer mistreatment may also reduce the extent to which service employees help out their coworkers or organization because it results in unfavorable job attitudes, which are one driver of citizenship behavior (e.g., Bateman & Organ, 1983). Unfortunately, previous studies have focused on customer mistreatment's relationship with citizenship behaviors directed at customers but not at coworkers or the organization (e.g., Shao & Skarlicki, 2014). However, indirect evidence suggests that customer mistreatment is negatively associated with organizational and interpersonal citizenship behaviors.…”
Section: Behavioral Criteriamentioning
confidence: 96%
See 1 more Smart Citation
“…Eastern cultural values are emphasized on collectivism (Shao & Skarlicki, 2014). In collectivistic societies, group goals are more important than personal goals (Zhang, Van Doorn, & Leeflang, 2014).…”
Section: Cultural Valuesmentioning
confidence: 99%
“…Building upon these scholarly works, we posit that psychological contract breach is important for understanding customer reaction to service failure. Shao and Skarlicki (2014), however, suggest that individuals vary in their propensity to take revenge (Shao and Skarlicki, 2014). Such variation could be caused by individual differences such as http://dx.doi.org/10.1016/j.ijhm.2015.07.011 0278-4319/© 2015 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 90%